Integrating E-Service quality, user satisfaction, and trust: A multi-model approach in higher education digital services - Agustinus Suradi; Mariana Windarti; Fery Firmansah; Beta Yudha Mahindarta (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2026)
The rapid digitalization of higher education services has intensified the need to understand the factors that shape user trust and satisfaction. While prior studies have emphasized the role of system and service quality, they have given limited attention to integrating organizational and contextual dimensions to explain user perceptions. This study addresses this gap by proposing an integrated model that combines the Technology–Organization–Environment (TOE) framework and the Information Systems Success Model (ISSM). Using a quantitative approach, data were collected via a survey of higher education users and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) and Confirmatory Composite Analysis (CCA). The results indicate that the proposed model demonstrates strong explanatory power (R² = 0.896) and predictive relevance, confirming its robustness in explaining user trust and satisfaction. The findings reveal that information quality is the most influential determinant, followed by organizational factors, while system quality and service quality show negligible effects. These results suggest a shift from a system-centric to an information-driven, context-oriented evaluation of digital services. This study contributes to the literature by extending the TOE and ISSM frameworks into a unified model and challenging traditional assumptions regarding the dominance of technical system attributes. Practically, the findings highlight the importance of higher education institutions prioritizing information quality and organizational readiness when designing user-centered digital services.